PROGRAM PENGEMBANGAN SOFT SKILL MAHASISWA “LITERASI DIGITAL BAGI KAUM MILENIAL” - Darmayanti, Putu Sri; Arianty, Anak Agung Ayu Arun Suwi; Susanti, Luh Eka; Aprinica, Ni Putu Isha; Paramitha, Made Widya; Rahayu, Ni Made Sri; Saputra, I Putu David Adi (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
This article provides an overview of the soft skill development program for students about digital literacy organized by the Diploma 3 Hospitality Study Program at Institut Pariwisata dan Bisnis Internasional on April 22 2022. The webinar carried out online via Zoom and aimed to provide knowledge in utilizing and using social media properly and wisely. This training program was attended by 148 Diploma 3 students. Several topics were conveyed by the speakers about digital literacy for millennials, namely the importance of digital literacy for millennials, especially students, the pros and cons and how to prevent the bad effect for Digital Literacy in millennials. The results of this activity were the students have more insight about digital literacy, be careful in voicing ideas or opinions before sharing them on social media, choose the right information, especially in finding learning resources and can directly interact with the speaker